Incidents and adverse events notified at hospital level - Andréia Mascarello; Aline Massaroli; Erica de Brito Pitilin; Jeferson Santos Araújo; Maria Eduarda Rodrigues; Jeane Barros de Souza (Rev Rene)
Objective: to identify the incidents and adverse events notified in a large size hospital. Methods: a retrospective study was carried out based on data extracted from handwritten notifications sheets, made available by the Patient Safety Nucleus of a large size hospital. The following variables were analyzed: type of incident, according to international safety goals; severity of the incidents with damage; and measures proposed to minimize the effects of the notified incident. Results: among the 1167 notifications, 653 (66.8%) of the incidents were related to pharmacovigilance, 563 (48.6%) presented as potential harm, 355 (28.7%) caused harm to the patient and of these, 228 (68.0%) were of mild intensity. Proposed actions were described in 705 (60.4%) of the notifications. Conclusion: the notifications allowed identifying a high number of incidents with potential to cause harm, denoting failures that could be minimized with the implementation of institutional protocols and professional training.